Clinical and epidemiological profile of pregnancy-induced hypertension (Salud, Arte y Cuidado, 2020)
Pregnancy-induced hypertension is found in pregnant women and indicates that they are at risk of serious complications such as pre-eclampsia and eclampsia. The objective was to determine the clinical and epidemiological profile of pregnant women in Hospital La Carucieña type 1. The study is descriptive with a quantitative, retrospective approach, non-experimental design and cross-sectional. The technique corresponds to a documentary observation by reviewing the medical records of the patients who attended the prenatal consultation. The results reflect that the signs and symptoms of the pathology were identified and exacerbated during pregnancy in all patients, headache being the predominant symptom in different weeks of gestational ages but predominantly early weeks, forcing them to go to the emergency service in a o several opportunities, in addition, in the first consultation to the emergency service, a significant increase in systolic and diastolic blood pressure figures was found, in the same way, it was identified that despite high blood pressure figures, most pregnant women do not use pharmacological treatment antihypertensive but only in those that merited several emergency consultations. It is concluded that it was identified in the same way that the pregnant women with the highest blood pressure figures were the primigravidae well above the multiparous ones and that likewise all the patients present a history of chronic arterial hypertension in some of their direct line relatives as a mother. or father, thus highlighting that despite being pregnancy-induced hypertension, it does not completely isolate it from pathological inheritance as a risk factor.
Keywords: clinical profile; epidemiological profile; gestational hypertension